2015
DOI: 10.3389/fnbeh.2015.00162
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptor–mTOR Activation is Required for the Antidepressant-Like Effects of Sarcosine during the Forced Swim Test in Rats: Insertion of AMPA Receptor may Play a Role

Abstract: Sarcosine, an endogenous amino acid, is a competitive inhibitor of the type I glycine transporter and an N-methyl-d-aspartate receptor (NMDAR) coagonist. Recently, we found that sarcosine, an NMDAR enhancer, can improve depression-related behaviors in rodents and humans. This result differs from previous studies, which have reported antidepressant effects of NMDAR antagonists. The mechanisms underlying the therapeutic response of sarcosine remain unknown. This study examines the role of mammalian target of rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…A recent study further confirmed that the metabolism of ketamine to (2S,6S;2R,6R)-hydroxynorketamine is essential for its antidepressant effects and the antidepressant actions of ketamine metabolites are independent of NMDAR inhibition but involve sustained activation of AMPARs (Zanos et al, 2016). Similarly, the antidepressant-like effect of sarcosine has been revealed through the activated AMPAR-mTOR signaling pathway (Chen et al, 2015). It still remains to be determined whether DMG also produced antidepressant-like effect through this pathway and how much involvement of its metabolite sarcosine.…”
Section: Discussionmentioning
confidence: 83%
“…A recent study further confirmed that the metabolism of ketamine to (2S,6S;2R,6R)-hydroxynorketamine is essential for its antidepressant effects and the antidepressant actions of ketamine metabolites are independent of NMDAR inhibition but involve sustained activation of AMPARs (Zanos et al, 2016). Similarly, the antidepressant-like effect of sarcosine has been revealed through the activated AMPAR-mTOR signaling pathway (Chen et al, 2015). It still remains to be determined whether DMG also produced antidepressant-like effect through this pathway and how much involvement of its metabolite sarcosine.…”
Section: Discussionmentioning
confidence: 83%
“…In rodent models, chronic sarcosine treatment significantly ameliorates the increased immobility induced by chronic unpredictable stress in the forced swim test (FST), a classical behavioral paradigm for measuring antidepressant action 46. In support of these findings, a single injection of sarcosine rapidly activates the mTOR signaling pathway, an effect abolished by rapamycin or AMPAR blockade, indicating that sarcosine exerts antidepressant-like effects by enhancing AMPAR-mTOR signaling pathway activity and by facilitating AMPAR membrane insertion 47. Rapastinel (formerly GLYX-13) is a novel synthetic compound that modulates the NMDAR in a glycine-like fashion when examined pharmacologically and electrophysiologically 48.…”
Section: Antidepressant Effects Induced By Enhancing Nmdar Activitymentioning
confidence: 84%
“…Among them, GLYX-13 has been proved to have sustained effects. On the other hand, D-serine (Malkesman et al 2012) and glycine transporter-I inhibitor sarcosine (Chen et al 2015;Huang et al 2013), which are assumed to potentiate NMDAR function through glycine site, can also improve depression-like behaviors in rodent models and in human depression (Huang et al 2013). Modulation of NMDAR glycine site might be majorly contributed to the rapid and sustained antidepressant-like effect of betaine, although betaine elevated 5-HT levels and has been suggested to be like a traditional antidepressant (Kim et al 2013).…”
Section: Discussionmentioning
confidence: 95%